2019
DOI: 10.1016/j.invent.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on ParentWorks: Learnings from the development and national roll-out of a self-directed online parenting intervention

Abstract: Online parenting interventions are an increasingly viable alternative to face-to-face programs, as they can potentially overcome barriers to participation and increase program reach. The current paper describes learnings from the design, development and dissemination of ParentWorks, a self-directed online parenting intervention designed to be inclusive of both mothers and fathers.ParentWorks was promoted via a national media campaign and was accessible to all Australian parents through a dedicated website. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…However, healthcare professional-led parent programmes have demonstrated better patient outcomes than selfdirected programmes. 34 Access to care Currently, there is no routine, standardised follow-up care and support provided to children and their parents following all critical illnesses and injuries in Australia. Furthermore, the geographical isolation of many Australian families and recent pandemic crises have highlighted the barriers to accessing traditional treatment services.…”
Section: Early Screening and Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, healthcare professional-led parent programmes have demonstrated better patient outcomes than selfdirected programmes. 34 Access to care Currently, there is no routine, standardised follow-up care and support provided to children and their parents following all critical illnesses and injuries in Australia. Furthermore, the geographical isolation of many Australian families and recent pandemic crises have highlighted the barriers to accessing traditional treatment services.…”
Section: Early Screening and Interventionmentioning
confidence: 99%
“…Self-directed parent programmes have greater potential for uptake as they do not require trained professionals to guide and can typically be implemented at a reduced cost. However, healthcare professional-led parent programmes have demonstrated better patient outcomes than self-directed programmes 34…”
Section: Introductionmentioning
confidence: 99%
“…That is a direct intervention by providing individual guidance to students at home (Collins et al, 2019). Then Cornett et al (2020) that teachers learn by visiting students' homes to support individual learning.…”
Section: Teacher Techniques For Students' Home Visitsmentioning
confidence: 99%
“…It is not conducive. They lack attention from parents or family because they work for a living (Collins et al, 2019;Al-Nasa'h et al, 2021). According to Li and Che (2022), all citizens continue to carry out the education and learning process with new adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…However, most existing programs are face to face, and the population-level benefits are hindered by an ongoing problem of low engagement levels, in part due to logistical difficulties (Finan et al, 2018). The online approach is one promising avenue to increase the reach of parenting programs, with online parenting programs such as ‘Triple P Online’ (Ralph and Sanders, 2004) for externalising problems and ‘Cool Little Kids Online’ (Morgan et al, 2015) for anxiety representing web-based versions of effective face-to-face programs (Collins et al, 2019; McLellan et al, 2017). However, there are currently no transdiagnostic online parenting interventions for clinical anxiety and depression in adolescents (Yap et al, 2017a) and a systematic review of technology-assisted parenting programs has found ‘Partners in Parenting’ (PiP) is the only program to target adolescent internalising problems (Hansen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%